2022
DOI: 10.1186/s12885-022-09553-w
|View full text |Cite
|
Sign up to set email alerts
|

A protocol to clinically evaluate liquid biopsies as a tool to speed up diagnosis of children and young adults with aggressive infection-related lymphoma in East Africa “(AI-REAL)”

Abstract: Background The capacity for invasive tissue biopsies followed by histopathology diagnosis in sub-Saharan Africa is severely limited. Consequently, many cancer patients are diagnosed late and outcomes are poor. Here, we propose to evaluate circulating tumour (ct) DNA analysis (“liquid biopsy”), a less invasive and faster approach to diagnose endemic EBV-driven lymphomas (EBVL) in East Africa. Methods We will evaluate the clinical utility of an alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The detailed design and study setting are described elsewhere. 10 For the portable WSI scanner validation, study pathologists evaluated 105 initially confirmed by gold standard pathology between February 2021 and December 2021. The sites included Kilimanjaro Christian Medical Centre (KCMC), Muhimbili National Hospital (MNH) in Tanzania, and St. Mary’s Hospital Lacor, Gulu, Uganda.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed design and study setting are described elsewhere. 10 For the portable WSI scanner validation, study pathologists evaluated 105 initially confirmed by gold standard pathology between February 2021 and December 2021. The sites included Kilimanjaro Christian Medical Centre (KCMC), Muhimbili National Hospital (MNH) in Tanzania, and St. Mary’s Hospital Lacor, Gulu, Uganda.…”
Section: Methodsmentioning
confidence: 99%
“…Formalin-fixed and paraffin-embedded (FFPE) tissue blocks of the identified cases were previously processed according to standard study protocol. 10 Specialist pathological assessment included a full immunohistochemistry (IHC) panel performed on the automated Roche Ventana Benchmark platform (Ventana Medical Systems Inc, USA) . For suspected Burkitt’slymphoma (BL) cases, c-MYC staining was performed in addition to using the Naresh algorithm Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because interaction with more established centres in HICs is critical, we recommend training for laboratory scientists through short courses to introduce specific technical skills and fellowships for more long-term mentoring with experts in centres of excellence situated in HICs. We acknowledge that achieving these goals goes beyond science and public health because it 2024 (Legason et al, 2022). In addition to a technical and clinical validation, the study addresses the need for regional multi-disciplinary diagnostic capacity building, laboratory quality control and health-economic evidence to achieve long-term sustainability and patient benefit that will ultimately catalyse multi-cancer early detection more generally.…”
Section: Feasibility Of Applying This Technology In Ssamentioning
confidence: 99%
“…In conclusion, cfDNA promises earlier and more precise diagnosis of eBL in SSA. The UK’s National Institute of Health Research (NIHR) has funded a multicentre study in Uganda and Tanzania that evaluates this promise with initial results expected to be published in 2024 (Legason et al, 2022 ). In addition to a technical and clinical validation, the study addresses the need for regional multi-disciplinary diagnostic capacity building, laboratory quality control and health-economic evidence to achieve long-term sustainability and patient benefit that will ultimately catalyse multi-cancer early detection more generally.…”
Section: Feasibility Of Applying This Technology In Ssamentioning
confidence: 99%